Toward Competency-Based Training: To What Extent Are We Competency-Based?. Issue 1 (29th June 2021) - Al-halabi, Becher; Bilgic, Elif; Vassiliou, Melina; Gilardino, Mirko
Abstract : Background: Time-based training models in plastic surgery vary in exposure, resulting in low confidence levels among graduates. The evolution of postgraduate medical education into a competency-based model to address these issues requires an understanding of interventions described in the plastic surgery literature to identify gaps and guide creation of assessments to demonstrate competence. Methods: A systematic search of the MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature, PubMed, and Cochrane databases from inception until December of 2017 was conducted using search terms and synonyms of educational interventions reported in plastic surgery. Full texts were retrieved following filtering and data extracted were related to intervention design and execution, involvement of competency assessment, and educational objectives and alignment to Accreditation Council for Graduate Medical Education competencies and Royal College of Physicians and Surgeons of Canada Canadian Medical Education Directives for Specialists roles. Study quality was assessed using Kirkpatrick's levels of learning evaluation, validity evidence, and the Medical Education Research Study Quality Instrument score. Results: Of the initial 4307 results, only 36 interventions met the inclusion criteria. Almost all interventions aligned to medical knowledge and patient care Accreditation Council for Graduate Medical Education competencies. One-fifth of the interventions involved no assessment of competency, whereas most displayed assessment at the level of design as opposed to outcomes. Quality assessment revealed low levels of learning evaluation and evidence of validity; the average Medical Education Research Study Quality Instrument score was 10.9 of 18. Conclusion: A systematic review of educational literature in plastic surgery was conducted to assess the quality of reported educational interventions, and to help guide creating tools that ensure competency acquirement among trainees.